IMPROVING MATHEMATICS LEARNING ACTIVITIES USING THINK-PAIR-SHARE COOPERATIVE LEARNING MODELS T FOR STUDENTS GRADE XI - Mifta Nur Khasanah; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The learning process, which is monotonous and has no variation, will make students bored easily. Even learning that focuses on the teacher's effects, students tend to be passive and not accustomed to showing their opinions. Most of them are seen to be silent when the learning process is going on. In that case, it needs an effort to improve students’ learning activity. This research is aimed to improve Mathematics learning activity with cooperative learning model type TPS (TPS) for students class XI Science 3 at State Senior High School (SMAN) 1 Dukun Magelang Regency in Academic Year 2017/ 2018. Data is gathered by using an observation sheet and interview. This research belongs to action research, which contains two cycles. The research subject is students of XI Science 3 SMAN 1 Dukun Magelang Regency in Academic Year 2017/ 2018. Whereas the object of the research is to improve students' Mathematics learning activity with cooperative learning model type, TPS for students class XI Science 3 at SMAN 1 Dukun Magelang Regency in Academic Year 2017/ 2018. In collecting the data, the writer uses an observation sheet and interview. The research results show that cooperative learning model type TPS can improve the Mathematics learning activity of XI Science 3 at SMAN 1 Dukun Magelang Regency in Academic Year 2017/ 2018. This case is proved from the result of the observation of Mathematics learning, which works out increasing on each cycle. On cycle, one average presentation of the result of students' observation of Mathematics learning activity is about 49,53%. On cycle II average presentation of the result of students' observation of Mathematics, learning activity is about 70,27%. From the interview result, it can be explained that common students are interested and feel pleased in learning Mathematics with cooperative learning model type TPS.